The Entrepreneurial Partnership in Strengthening Entrepreneurial Resilience of Fishermen Communities in Sidoarjo City - Hambalah, Febrina; Herman, Herman; Fatmawati, Rini; Maharani, Ragita Puan; Wardani, Citra Dewi Ayu Kusuma (Universitas Proklamasi 45, 2025)
The partnerships that had been established by entrepreneurs in the Fishermen's Community in Tambak Cemandi village, Sidoarjo, Indonesia, had not yet determined to be effective. This research aimed to explain the role of entrepreneurial partnerships in strengthening the entrepreneurial resilience of entrepreneurs in the fishermen’s community in Tambak Cemandi village, Sidoarjo, Indonesia. The research method used was descriptive qualitative, with data collection techniques through in-depth interviews, documentation, and literature study. The results of this research showed that the majority of entrepreneurial partnerships that had taken place so far had been with investors and suppliers. Meanwhile, the Government, business associations, and distribution partners still had a minimal role in this entrepreneurial partnership. Therefore, the entrepreneurial resilience within the fishermen’s community in Tambak Cemandi, Sidoarjo, Indonesia is still not fully optimized.